Enhanced Stress Resilience Training in Surgeons: Iterative Adaptation and Biopsychosocial Effects in 2 Small Randomized Trials - Lebares, Carter C. (Ann Surg, 2021)
OBJECTIVE: To determine the effects of ESRT (an iteratively adapted and tailored MBI) on perceived stress, executive cognitive function, psychosocial well-being (ie, burnout, mindfulness), and pro-inflammatory gene expression in surgical (ESRT-1) and mixed specialty (ESRT-2) PGY-1 volunteers. SUMMARY OF BACKGROUND AND DATA: Tailored MBIs have proven beneficial in multiple high-stress and high-performance populations. in surgeons, tailored MBIs have been shown to be feasible and potentially beneficial, but whether mindfulness-based cognitive training can improve perceived stress, executive function, well-being or physiological distress in surgical and nonsurgical trainees is unknown. METHODS: In 2 small single-institution randomized clinical trials, ESRT, a tailored mindfulness-based cognitive training program, was administered and iteratively adapted for first-year surgical (ESRT-1, 8 weekly, 2-hour classes, n = 44) and mixed specialty (ESRT-2, 6 weekly, 90-minute classes, n = 45) resident trainees. Primary and secondary outcomes were, respectively, perceived stress and executive function. other prespecified outcomes were burnout (assessed via Maslach Burnout Inventory), mindfulness (assessed via Cognitive Affective Mindfulness Scale - Revised), and pro-inflammatory gene expression (assessed through the leukocyte transcriptome profile “conserved transcriptional response to adversity”). RESULTS: Neither version of ESRT appeared to affect perceived stress. Higher executive function and mindfulness scores were seen in ESRT-1, and lower emotional exhaustion and depersonalization scores in ESRT-2, at pre-/post-intervention and/or 50-week follow-up (ESRT-1) or at 32-week follow-up (ESRT-2), compared to controls. Pooled analysis of both trials found ESRT-treated participants had reduced pro-inflammatory RNA expression compared to controls. CONCLUSIONS: This pilot work suggests ESRT can variably benefit executive function, burnout, and physiologic distress in PGY-1 trainees, with potential for tailoring to optimize effects.